2012
DOI: 10.1111/tbj.12039
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Cell Change With Atypia (Flat Epithelial Atypia) on Breast Core Biopsy-Outcomes Following Open Excision

Abstract: Columnar cell change with atypia (CCCA) is a relatively recently recognized pathologic breast entity considered to be a risk factor for subsequent development of breast carcinoma. The aim of this study was to investigate the significance of finding CCCA on breast core biopsy, by establishing the frequency of other breast pathology on subsequently performed surgical excision specimens. All cases with CCCA as the most advanced lesion on core biopsy were reviewed. After excision, another advanced proliferative le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…An issue in the current clinical management of FEA is the question of surgical excision when FEA is diagnosed with core needle biopsy. Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision . This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…An issue in the current clinical management of FEA is the question of surgical excision when FEA is diagnosed with core needle biopsy. Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision . This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH.…”
Section: Discussionsupporting
confidence: 57%
“…This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH. In addition to a small risk of detecting cancer at the time of surgical excision, multiple studies have reported finding other high‐risk lesions (AH or lobular carcinoma in situ) in 20% to 52% of women undergoing excision of FEA found at core needle biopsy . Although the majority of studies recommend surgical excision for FEA detected on core needle biopsy, others have suggested that this might not be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in our systematic review, CCL-A diagnosed in core needle biopsies showed the presence of cancer in 9.4% of the subsequent excisions. 14 In more recent publications the underestimation risks ranged between 3.2% and 19%, [15][16][17][18][19][20][21][22][23][24] dependent upon study method differences, as some of the studies did not take into account radiological findings and radiological-pathological discordances. In larger vacuum biopsies more material is investigated, often showing lower underestimation risks [sometimes with no (in-situ) cancer] in subsequent excision biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of these which were malignant on excision remained unchanged at around 14%. Biggar reviewed 51 cases at the WBC from 2006–10, in which columnar cell change with atypia (or FEA) was the most advanced finding on core biopsy or VAB. On excision, 6% were found to have malignancy and a further 14% were found to have other significant lesions (ADH, atypical lobular hyperplasia or lobular carcinoma in situ).…”
Section: Discussionmentioning
confidence: 99%